2004
DOI: 10.1002/chin.200446293
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in Chinese Herbal Medicines: A Biochemical Perspective

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 1 publication
4
83
0
Order By: Relevance
“…Oxidative stress is the state of imbalance between the level of antioxidant defence system and production of the oxygen derived species [23] . The increased level of oxygen and oxygen derived species such as superoxide radicals, hydroxyl radicals and peroxide radicals causes the oxidative stress [24] . The in vitro assays such as DPPH radical scavenging assay, superoxide radical scavenging assay, hydroxyl radical scavenging assay, lipid peroxide radical scavenging assay suggest the ability of the L. racemosa leaf extract to reduce the biological oxidative stress [25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is the state of imbalance between the level of antioxidant defence system and production of the oxygen derived species [23] . The increased level of oxygen and oxygen derived species such as superoxide radicals, hydroxyl radicals and peroxide radicals causes the oxidative stress [24] . The in vitro assays such as DPPH radical scavenging assay, superoxide radical scavenging assay, hydroxyl radical scavenging assay, lipid peroxide radical scavenging assay suggest the ability of the L. racemosa leaf extract to reduce the biological oxidative stress [25,26] .…”
Section: Discussionmentioning
confidence: 99%
“…Increased O 2 concentration and production of oxygen-derived species such as superoxide radical ( O 2 À ), hydroxyl radical (OH ) and hydrogen peroxide cause oxidative stress [21]. DPPH and superoxide radical scavenging activity assays indicated that TFLA and quercetin were capable of scavenging DPPH and superoxide radicals in a dose dependent manner, thus suggesting the ability of TFLA to ameliorate oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Natural antioxidants including superoxide dismutase, catalase and glutathione peroxidase are depleted accompanied by accumulation of reactive oxygen species. In such a situation, natural products can play an important role in two aspects: enhance the activity of original natural antioxidants and neutralize reactive oxygen species by nonenzymatic mechanisms [21]. Oxidative stress is considered to play a prominent causative role in many diseases including liver damage [22].…”
Section: Discussionmentioning
confidence: 99%
“…A number of these plants from other continents have been reported to exert therapeutic efficacies through their antioxidant activities (Aruoma, 2003;Park, Pezzuto, 2002;Scartezzini, Speroni, 2000;Zhu et al, 2004) Ipomoea asarifolia, Roemer & J.A. Schultes (synonyms: Ipomoea hederifolia) or Morning glory, known in the Hausa language of Nigeria as "Duman Karda" (Kaduna), "Duman ra'afii" (Kano) and "Woba boje" or "Daadi mayo" (Adamawa), is a hairless, succulent perennial weed of the family Convolvulaceae that grows in hydromorphic soils in low lying and inland valleys, streams, and river banks of temperate and tropical countries (Okozie, Agyakwa, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…A number of these plants from other continents have been reported to exert therapeutic efficacies through their antioxidant activities (Aruoma, 2003;Park, Pezzuto, 2002;Scartezzini, Speroni, 2000;Zhu et al, 2004), but only a few Nigerian and African medicinal plants have been the focus of research (Atawodi, 2005). Ipomoea asarifolia, Roemer & J.A.…”
Section: Introductionmentioning
confidence: 99%